Influence of dibenzyl ether (DBE) addition on the structure of chromium carbide coating obtained by the MOCVD method from COL "BARKHOS" - Krokhmal, S.A.; Zueva, T.N. (Вопросы атомной науки и техники, 2021)
Investigations of the effect of the addition of dibenzyl ether (DBE) to the chromium organic liquid (COL) “Barkhos” on the structure and performance properties of chromium carbide coatings obtained by chemical deposition of their gas phase have been carried out. It is shown that the use of the DBE additive expands the temperature range for the formation of chromium carbide coatings with a horizontally layered structure, which are more resistant to corrosion and erosion wear. In this case, there is an increase in the adhesive strength and cavitation resistance of the coatings. The use of the DBE additive reduces the through porosity of the coatings. Coatings obtained with DBE additives have an abnormally high resistance to electrochemical dissolution in comparison with other materials used for work in corrosive environments.